The Analysis Of Serabi Quality Resulting From Pumpkin Subtitution - Rahmi Holinesti; Isnaini Isnaini (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
This research is motivated by the many people who do not know the benefit of pumpkin for health so that the pumpkin is underutilized in food products, event though pumpkin has many benefits, one of which is an antioxidant and contains beta-caroten. Besides, the use of pumpkin is expected to increase the nutritional value of serabi as while as a natural dye in functional food products. The aim of this research to analyze the effect of the pumpkin substitution as much as 0%, 15%, 25%, and 35%, against volume, the shape, color, texture, level, and taste of serabi result. The kind of study is a pure experiment that used a completely random design method. The use of data is primary data sources are five trained panelists who give answers from angkettes or organoleptic test formats. The data analysis used ANAVA. If there is a significant effect, then proceed with Duncan’s test. Research shows that there is the influence of pumpkin substitution on the quality of color and texture. Meanwhile, there is no apparent effect on the quality of the volume, shape, flavor, and taste. The best result of the study was in the use of pumpkin by 35% (X3) for volume quality, shape, flavor, texture, and taste on serabi.